The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1088/1748-9326/ab4433
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of emerging biotechnologies

Abstract: Research on public views of biotechnology has centered on genetically modified (GM) foods. However, as the breadth of biotechnology applications grows, a better understanding of public concerns about non-agricultural biotechnology products is needed in order to develop proactive strategies to address these concerns. Here, we explore the perceived benefits and risks associated with five biotechnology products and how those perceptions translate into public opinion about the use and regulation of biotechnology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Well-educated female participants and those living in larger cities were more reluctant [26]. Conversely, Azodi et al (2019) found no association between education level and positive opinion about biotechnology [27]. Fernbach et al (2019) argue that the more the extremism of the opposition to genetically modified foods increases, the more objective knowledge of the matter decreases.…”
Section: Discussionmentioning
confidence: 89%
“…Well-educated female participants and those living in larger cities were more reluctant [26]. Conversely, Azodi et al (2019) found no association between education level and positive opinion about biotechnology [27]. Fernbach et al (2019) argue that the more the extremism of the opposition to genetically modified foods increases, the more objective knowledge of the matter decreases.…”
Section: Discussionmentioning
confidence: 89%
“…Public perception analyses of biotechnology have historically focused on GM foods. However, it has been found that society at large is massively supportive of developments in non-agricultural biotechnology, such as the development of new drugs and vaccines (Azodi & Dietz, 2019). Despite the fact that GM crops help reduce greenhouse gas emissions, are more resistant to diseases and pests, produce more and provide more nutrients to humans and animals, society in general, and especially in the European Union, has a low acceptance level (Woźniak et al, 2021).…”
Section: Project-based Learning (Pbl)mentioning
confidence: 99%